Influence on the quality of life of Medicine students related to bad food and sleep (Research, Society and Development, 2021)
The poor quality of life of health students is closely related to some variables, such as eating and sleeping disorders. Health students receive information about adequate nutrition; however, this does not imply that this knowledge is followed by appropriate eating behaviors. Regarding sleep, which is a fundamental element for human health, since it is involved in multiple systemic physiological mechanisms, it is known that the physiological need for sleep varies a lot according to age. Typically, young adults need, on average, seven to nine hours of sleep per night. Thus, the present study aims to elucidate the main factors related to poor quality of food and sleep-in health students and the consequences of these habits on the body and academic performance. An integrative review of studies of the literature was obtained by searching the databases: PubMed, SciELO and VHL, using the descriptors: eating behavior, medical students, sleep disorders. Studies published between 2015 and 2020 in Portuguese, English and Spanish were included. From these data, a compilation of the most relevant information for the construction of this work was made. It was found that medical students have unhealthy eating habits, being characterized by low consumption of vegetables, fruits and water, and a greater intake of red meat, processed foods, and sweets. The literature shows a close correlation between body imagery and eating behavior. Poor sleep quality is correlated with superficial learning by university students in the health field. There is also a close link between short sleep duration and increased chances of developing hyperlipidemia, car accidents and coronary artery disease. The various risk factors for chronic noncommunicable diseases in health students were presented, among which neoplasms, metabolic disorders, diseases of the nervous, respiratory, cardiovascular and osteoarticular systems stand out, mainly. Thus, the results show the differences between lifestyle and what is recommended, especially in relation to sleep and food intake. This research contributes to obtaining more information about the factors that influence the illness process in university students, especially academics in the health area.